INTERNATIONAL CENTER FOR THE SETTLEMENT OF DISPUTES UNDER THE AUSPICES OF THE ECONOMIC COURT OF THE COMMONWEALTH OF INDEPENDENT STATES: BENEFITS FOR ECONOMIC AGENTS - Kamenkova , Людмила Эдуардовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In this article structure and functions of the International Center for the Settlement of Disputes under the Auspices of the Economic Court of the Commonwealth of Independent States are considered, the procedure of case consideration in the Arbitration Court and the order of mediation procedures are described.